Preparation of multi-coal synergistic fast-charging graphite negative electrode material and lithium ion battery
Patent Information
- Application Number
- CN202511899317.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-16
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-12-16
AI Technical Summary
[0004]目前,尚未见有技术方案系统性地将高镜质组煤的易石墨化特性、中变质程度煤的粘结特性与高惰质组煤的骨架造孔特性三者结合,以在显著降低石墨化温度的同时,构建优化的孔隙结构用于提升快充性能
[0032]1.显著降低能耗:通过高镜质组煤的催化作用和原位铁催化剂的引入,将最终石墨化温度从传统的2800℃以上成功降低至2300~2500℃,大幅节约了生产成本。
Smart Images

Figure CN121672511B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery anode material technology, specifically relating to the preparation of a fast-charging graphite anode material with synergistic effects of multiple coal types and lithium-ion batteries. Background Technology
[0002] Artificial graphite is currently the mainstream graphite-based anode material for lithium-ion batteries. Traditional coke-based anodes, due to their large-diameter layered structure, result in long lithium-ion migration paths, which can easily lead to severe polarization and lithium dendrite precipitation during high-current fast charging. To improve the fast-charging performance of graphite anodes, it is usually necessary to perform pore-forming, coating, granulation, or structural modification on the graphite material. Existing pore-forming technologies mostly use chemical reagents (such as KOH chemical activation, sodium bicarbonate (CN202310263813.9), potassium gas activation (CN202311103558.8)) activation methods (water vapor has extremely limited activation ability for graphite), resulting in significant pollution, high cost, and complex exhaust gas treatment. On the other hand, methods that lower the temperature through catalytic graphitization often suffer from catalyst residues that affect the battery's cycle life and other electrochemical performance. Pre-intercalation of lithium is extremely expensive.
[0003] Anthracite and other coal-based raw materials are potential inexpensive precursors for the preparation of artificial graphite. Among the microscopic components of coal, the vitrinite begins to form an ordered graphite structure at about 2300℃, and is easily graphitized due to its large number of aliphatic side chains and weak bonds; while the inertinite has a high degree of aromatization and only begins to slowly graphitize at temperatures above 2500℃, but its rigid structure can serve as a physical framework.
[0004] Currently, there is no systematic technical solution that combines the graphitization characteristics of high vitrinite coal, the bonding characteristics of medium metamorphic coal, and the pore-forming characteristics of high inert coal to construct an optimized pore structure to improve fast-charging performance while significantly reducing the graphitization temperature. Summary of the Invention
[0005] To address the aforementioned technical problems, the present invention aims to provide a fast-charging graphite anode material with synergistic effects of multiple coal types, its preparation method, and a lithium-ion battery. By complementing the characteristics of different coal types and synergistically utilizing the process, the graphitization temperature is significantly reduced, and a porous and soft / hard carbon composite structure is constructed in situ, thereby achieving excellent fast-charging performance and cycle stability.
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0007] A method for preparing a fast-charging graphite anode material with synergistic effects of multiple coal types includes the following steps:
[0008] Step 1: Reduce the ash content of coal types A, B, and C to 0.5-5 wt% through gravity separation and flotation processes.
[0009] The A type of coal is easily graphitized coal, selected from lignite or long-flame coal with a vitrinite content ≥60%; it has a low degree of coalification and is rich in volatile matter and active components such as structural defects and chemical impurity atoms, which serve as graphitization catalysts and "nucleation sites" for graphitization, while also utilizing its high volatile matter advantage as a source of micropore formation; the median particle size D50 of the A type of coal is 0.5~5μm.
[0010] The B coal type is a structural skeleton coal, selected from one or more of anthracite and lean coal with an inertinite content ≥50%; it has a high carbon content and a dense structure, serving as the main body of the final graphite skeleton; the median particle size D50 of the B coal type is 8~15μm.
[0011] The C type of coal is a caking and pore-forming coal, selected from one or more of gas coal, gas-rich coal, 1 / 3 coking coal, coking coal, lean coal, or fat coal; it has a certain degree of caking properties and serves as a binder and in-situ pore-forming agent. The median particle size D50 of the C type of coal is 1~5μm;
[0012] Step 2: Coal type A is embedded into the surface of coal type B through mechanical fusion, with a mass ratio of coal type A to coal type B of 1:2 to 1:5. Then, the fused material is placed in a carbonization furnace and heated to 650 to 900°C at 0.5 to 5°C / min under an inert atmosphere for the first stage of heat treatment, and held for 2 to 4 hours to obtain a pre-carbonized material of the mixture of coal type A and coal type B. During this process, a large amount of volatiles generated by coal type A, as well as active hydrogen generated by the condensation reaction between hydrogen free radicals during the fracture of the macromolecular structure in the coal and the condensation reaction of semi-coke at high temperature, activate the surface of the inert group structure of coal type B and perform preliminary etching to form pores or structural defects, and promote the further transformation of the disordered carbon structure of coal type B into a morphology that is easy to graphitize to obtain a mixture of coal type A and coal type B.
[0013] Step 3: Mix the pre-carbonized material of the mixture of coal type A and coal type B with coal type C at a mass ratio of 100:(5-20); under an inert atmosphere, heat to 350-500℃ at 10-20℃ / min for the second stage of heat treatment, hold the temperature for 2-3 hours, and then heat to 700-900℃ at the same heating rate and hold the temperature for 0.5-1 hours to form a composite precursor of multiple coal types;
[0014] At this temperature, coal type C, under suitable conditions, produces a large amount of tar and gas. These liquids, gases, and residual coal particles together form a colloidal state, acting as a binder to bind the particles formed from coal types A and B into secondary particles. Simultaneously, FeS2 in coal type C decomposes, sulfur escapes in gaseous form, producing an etching effect, while iron is reduced to elemental or lower valence states, remaining in the system as an in-situ catalyst. This step achieves particle integration and the introduction of mesopores / macropores, forming a composite precursor of multiple coal types.
[0015] Step 4: The composite precursor of multiple coal types is heated to 2300℃~2800℃ according to the heating curve, and graphitized. The temperature is held for 10~24 hours to obtain coal-based graphite.
[0016] Step 5: The coal-based graphite is sequentially screened, demagnetized, and packaged to obtain coal-based fast-charging graphite anode material.
[0017] Furthermore, in step 1, the grinding particle size of coal type A must satisfy (D90-D10) / D50≤0.8, the grinding particle size of coal type B must satisfy (D90-D10) / D50≤1.6, and the grinding particle size of coal type C must satisfy (D90-D10) / D50≤2.0.
[0018] Furthermore, in step 1, the volatile matter content of coal type A (easily graphitized coal) is ≥30%, and the fixed carbon content of coal type B (structural skeleton coal) is ≥75%.
[0019] Furthermore, coal type C can be high-sulfur coal with a sulfur content of 1-4 wt%, and the sulfur content of pyrite accounts for ≥40%;
[0020] Furthermore, coal type C (caking coal) contains inorganic sulfur, mainly FeS2, at a content of 1-5 wt%.
[0021] Furthermore, in step 2, coal type A is embedded into the surface of coal type B through mechanical fusion, and the effect satisfies that the surface peeling force for separating coal type A from coal type B is 0.08~0.12 N / mm.
[0022] Furthermore, in step 2, when embedding coal type A onto the surface of coal type B through mechanical fusion, 1-5 wt% of binder is added, and mechanical fusion is carried out at a high temperature of 10-50°C above the softening point of asphalt. The binder is selected from one or more of resin, asphalt, starch, and lignin. If the binder is asphalt or lignin, the fusion temperature should be 10-40°C higher than its softening temperature; if the binder is resin, the fusion temperature should be 20-50°C higher than the glass transition temperature of the resin.
[0023] Furthermore, the inert atmosphere in step 2 is a mixture of hydrogen and an inert gas, with hydrogen accounting for 5-10% of the volume; the inert gas is one or more of nitrogen, argon, and helium.
[0024] This invention fully utilizes the catalytic and early-stage activation effects of high volatile matter and low metamorphism of coal type A. Simultaneously, after preliminary carbonization, the structural defects in the carbon material (such as vacancies, surface defects, functional groups, disordered graphite layer edges, and dangling bonds) and residual chemical impurities (such as non-metallic inclusions, carbides, alkali metals, and alkaline earth metals) become the main graphitization "nucleation sites" (heterogeneous nucleation centers, reducing interfacial energy) during the graphitization process. Furthermore, the in-situ iron catalytic mechanism introduced by coal type C significantly reduces the graphitization temperature of the entire composite system to 2300-2800℃ (far lower than the >3000℃ required by traditional anthracite). During this process, the carbon skeleton of coal type B is fully graphitized, forming the main conductive network, while the pores generated by coal types A and C are preserved and shaped, ultimately forming a highly crystalline graphite material with abundant hierarchical pores.
[0025] This invention provides a fast-charging graphite anode material with synergistic effects of multiple coal types, prepared by the above method. It consists of secondary particles formed by the fusion of primary particles, characterized by a hierarchical pore structure, including micropores (<2 nm) originating from coal type A, mesopores (2~50 nm) etched from sulfur (including organic and inorganic sulfur) originating from coal type C, and macropores (>50 nm) between secondary particles.
[0026] These voids undergo secondary evolution during graphitization, such as partial closure or pore size reduction. Therefore, their content is insufficient to cause a sudden increase in specific surface area, leading to a lower initial coulombic efficiency, but they do form rapid lithium-ion shuttle channels. After high graphitization, XRD testing shows that the interlayer spacing d of the (002) crystal planes... 002 ≤0.336 nm, orientation degree ≥80.
[0027] When used as a negative electrode for lithium-ion batteries, it exhibits high reversible capacity (≥350 mAh / g) and excellent fast charging performance (capacity retention ≥85% at 6C charge / discharge rate).
[0028] An ion battery is assembled by referring to the method of GB / T44027.1-2024 with the coal-based fast-charging graphite anode material, conductive agent and binder, and its electrochemical performance is tested.
[0029] Furthermore, using NCA as the positive electrode, a fast-charging battery with a fast-charging characteristic of 6C or higher is assembled, and the internal resistance is ≤15mΩ.
[0030] Furthermore, the negative electrode employs a layered coating method to ensure that the longitudinal surface density difference of the negative electrode is ≤0.12 mg·cm³. -2 After roller pressing, its compacted density should be controlled below 1.5 g / cm³; the nitrogen specific surface area of the conductive agent used should be ≤20 m². 2 / g.
[0031] This invention utilizes a variety of inexpensive and abundant coal sources as raw materials. It fully leverages the structural defects within coal that are present in various thermodynamically high-energy states, the ease with which volatile matter in coal forms pores, the low graphitization temperature of the vitrinite group, and the high aromatization degree and high graphitization temperature of the inertinite group. Through multi-coal composite technology, it achieves a simple and mild process for the preparation of artificial graphite, significantly reducing the difficulty of industrial scale-up. This is a highly cost-effective technical approach. Compared with existing technologies, this invention has the following advantages:
[0032] 1. Significantly reduced energy consumption: Through the catalytic effect of high vitrinite coal and the introduction of in-situ iron catalyst, the final graphitization temperature was successfully reduced from the traditional 2800℃ or above to 2300~2500℃, which greatly saved production costs.
[0033] 2. Optimized pore structure: By utilizing the characteristics of different coal types at different heat treatment stages, a hierarchical pore system of micropores-mesopores-macropores was constructed in situ, providing abundant migration channels and storage sites for lithium ions, which greatly improves fast charging performance.
[0034] 3. Outstanding synergistic effect: The three types of coal, A, B and C, respectively play the roles of "catalyst pore formation", "skeleton" and "bonding pore formation agent" in the preparation process. The process steps are closely linked, achieving a synergistic effect of 1+1+1>3.
[0035] 4. Green and cost advantages: It avoids the use of chemical pore-forming agents such as strong acids and strong alkalis, has low raw material costs, and the process is highly compatible with existing graphite production lines, making it suitable for industrial production. Attached Figure Description
[0036] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0037] Figure 1 Example 2 of the present invention: XRD pattern of coal-based graphite (silicon internal standard method).
[0038] Figure 2 Example 2 of the present invention: the first charge-discharge curve of coal-based graphite.
[0039] Figure 3 Example 2 of the present invention: Ratio performance curve of coal-based graphite.
[0040] Figure 4 SEM image of coal-based graphite in Example 2 of this invention.
[0041] Figure 5 TEM image of coal-based graphite in Example 2 of this invention.
[0042] Figure 6 XRD pattern of coal-based graphite (silicon internal standard method) in Comparative Example 1 of this invention.
[0043] Figure 7 The first charge-discharge curve of anthracite-based graphite in Comparative Example 1 of this invention.
[0044] Figure 8 The rate performance curve of anthracite-based graphite in Comparative Example 1 of this invention. Detailed Implementation
[0045] To gain a deeper understanding of this invention, we will provide a comprehensive and detailed description. However, this invention has various implementations and is not limited to the specific examples listed herein. These examples are presented to enhance a full understanding of the disclosure of this invention.
[0046] Example 1:
[0047] Step 1: Select low-ash Xinjiang long-flame coal (vitrinite content 70%) as coal type A, reduce its ash content to 2.0 wt% through gravity separation and flotation processes, and then grind it to a D50 of 2 μm; select Taixi anthracite (fixed carbon content 88%) as coal type B, reduce its ash content to 5.0 wt% through gravity separation and flotation processes, and then grind it to a D50 of 12 μm; select Shanxi coking coal as coal type C, reduce its ash content to 4.0 wt% through gravity separation and flotation processes, and then grind it to a D50 of 3 μm;
[0048] Step 2: Add coal type A and coal type B to the mechanical fusion machine at a mass ratio of 1:5. Start the mechanical fusion machine and run it for 20 minutes. Under mechanical force, coal type A will be embedded into the surface of coal type B. The fused mixture will be heated to 750℃ at a rate of 5℃ / min and held at that temperature for 2 hours to obtain pre-carbonized material.
[0049] Step 3: Bonding and In-situ Hole Formation: The pre-carbonized material of the mixture of coal type A and coal type B obtained in Step 2 is mixed with coal type C at a mass ratio of 100:5. After uniform mixing, the second stage of heat treatment is carried out under an argon atmosphere. Specifically, the temperature is increased to 500℃ at a rate of 10℃ / min and kept at a constant temperature for 2.5 hours; then the temperature is increased to 900℃ at the same rate and kept at a constant temperature for 1 hour.
[0050] Step 4: Graphitization step: The multi-coal composite precursor obtained in step 3 is placed in an experimental induction graphitization furnace and heated to 2300℃ according to the preset heating curve for graphitization treatment. The temperature is then held at the highest temperature for 10 hours.
[0051] Step 5: Post-processing steps: The coal-based graphite obtained in Step 4 is sequentially screened, demagnetized, and packaged to obtain coal-based fast-charging graphite anode material.
[0052] Step 6: Fabrication of fast-charging battery: Assemble the coal-based fast-charging graphite, conductive graphite, and binder prepared in Step 5 into a battery according to the method in GB / T44027.1-2024, and test its electrochemical performance.
[0053] Example 2:
[0054] Step 1: Select low-ash Shaanxi long-flame coal (vitrinite content approximately 65%) as coal type A, reduce its ash content to 3.0 wt% through gravity separation and flotation processes, and then grind it to a D50 of 0.5 μm; select Shanxi anthracite (fixed carbon content 89%) as coal type B, reduce its ash content to 2.5 wt% through gravity separation and flotation processes, and then grind it to a D50 of 8 μm; select high-sulfur coking coal from Guizhou as coal type C, with a sulfur content of 5 wt%, reduce its ash content to 5.0 wt% through gravity separation and flotation processes, and then grind it to a D50 of 1 μm;
[0055] Step 2: Add coal type A and coal type B to the mechanical fusion machine at a mass ratio of 1:2, and add petroleum asphalt with a softening point of 150℃, at a rate of 5% of the total mass of coal types A and B. Start the mechanical fusion machine and heat it to 190℃ for 40 minutes. Under the action of mechanical force and binder, coal type A is embedded into the surface of coal type B. After mechanical fusion, the surface peeling force of coal type A separated from coal type B is 0.12 N / mm. Heat the fused mixture to 900℃ at a rate of 0.5℃ / min and hold for 4 hours to obtain pre-carbonized material.
[0056] Step 3: Bonding and In-situ Hole Formation: The pre-carbonized material of the mixture of coal type A and coal type B obtained in Step 2 is mixed with coal type C at a mass ratio of 100:10. After uniform mixing, the second stage of heat treatment is carried out under a nitrogen atmosphere. Specifically, the temperature is increased to 400℃ at a rate of 15℃ / min and kept at a constant temperature for 3 hours; then the temperature is increased to 800℃ at the same rate and kept at a constant temperature for 1 hour.
[0057] Step 4: Graphitization step: The composite precursor of multiple coal types obtained in step 3 is placed in a microwave-assisted graphitization furnace and heated to 2800℃ according to the preset heating curve for graphitization treatment. The temperature is then maintained at the highest temperature for 24 hours.
[0058] Step 5: Post-processing steps: The coal-based graphite obtained in Step 4 is sequentially screened, demagnetized, and packaged to obtain coal-based fast-charging graphite anode material.
[0059] Step 6: Fabrication of fast-charging battery: Assemble the coal-based fast-charging graphite, conductive carbon black, and binder prepared in Step 5 into a battery according to the method in GB / T44027.1-2024, and test its electrochemical performance.
[0060] Example 3:
[0061] Step 1: Select Xinjiang ultra-low ash lignite (vitrinite content 80%) as coal type A, and reduce its ash content to 2.0 wt% through gravity separation and flotation processes, then grind it to D50 of 5 μm, while controlling the particle size distribution (D90-D10) / D50=0.7; select Taixi anthracite (fixed carbon content 88%) as coal type B, and reduce its ash content to 0.5 wt% through gravity separation and flotation processes, then grind it to D50 of 15 μm, while controlling the particle size distribution (D90-D10) / D50=1.6; select Shanxi gas-rich coal as coal type C, and reduce its ash content to 4.0 wt% through gravity separation and flotation processes, then grind it to D50 of 3 μm, while controlling the particle size distribution (D90-D10) / D50=1.7;
[0062] Step 2: Add coal type A and coal type B to the mechanical fusion machine at a mass ratio of 1:4, along with phenolic resin at 1% of the total mass of coal types A and B. Start the mechanical fusion machine and heat it to 120℃ for 25 minutes. Under the action of mechanical force and binder, coal type A is embedded into the surface of coal type B. After mechanical fusion, the surface peeling force of coal type A separated from coal type B is 0.08 N / mm. Heat the fused mixture to 650℃ at a rate of 2℃ / min and hold for 3 hours to obtain pre-carbonized material.
[0063] Step 3: Bonding and In-situ Hole Formation: The pre-carbonized material of the mixture of coal type A and coal type B obtained in Step 2 is mixed with coal type C at a mass ratio of 100:20. After uniform mixing, the second stage of heat treatment is carried out under an argon atmosphere. Specifically, the temperature is increased to 350℃ at a rate of 20℃ / min and kept at a constant temperature for 2 hours; then the temperature is increased to 700℃ at the same rate and kept at a constant temperature for 0.8 hours.
[0064] Step 4: Graphitization step: The composite precursor of multiple coal types obtained in step 3 is placed in an Atchison crucible graphitization furnace and heated to 2800℃ according to the preset heating curve for graphitization treatment. The temperature is then held at the highest temperature for 20 hours.
[0065] Step 5: Post-processing steps: The coal-based graphite obtained in Step 4 is sequentially screened, demagnetized, and packaged to obtain coal-based fast-charging graphite anode material.
[0066] Step 6: Fabrication of the fast-charging battery: Using the coal-based fast-charging graphite, conductive carbon black, and conductive graphite prepared in Step 5 as conductive agents and binders, assemble the battery according to the method in GB / T44027.1-2024, and test its electrochemical performance. The negative electrode is prepared using a layered coating method to ensure a longitudinal surface density difference of 0.1 mg·cm⁻¹. -2 After being rolled, its compacted density is 1.2 g / cm³. 3 .
[0067] Example 4:
[0068] Step 1: Select low-ash Xinjiang long-flame coal (vitrinite content 60%) as coal type A, reduce its ash content to 2.0 wt% through gravity separation and flotation processes, and then grind it to a D50 of 3 μm; select Yunnan anthracite (fixed carbon content 87%) as coal type B, reduce its ash content to 1.5 wt% through gravity separation and flotation processes, and then grind it to a D50 of 10 μm; select lean coal from Shanxi as coal type C, reduce its ash content to 3.0 wt% through gravity separation and flotation processes, and then grind it to a D50 of 5 μm;
[0069] Step 2: Add coal type A and coal type B to the mechanical fusion machine at a mass ratio of 1:3. Start the mechanical fusion machine and run it for 50 minutes. Under mechanical force, coal type A will be embedded into the surface of coal type B. The fused mixture will be heated to 800℃ at a rate of 4℃ / min and held at that temperature for 3 hours to obtain pre-carbonized material.
[0070] Step 3: Bonding and In-situ Hole Formation: The pre-carbonized material of the mixture of coal type A and coal type B obtained in Step 2 is mixed with coal type C at a mass ratio of 100:15. After uniform mixing, the second stage of heat treatment is carried out under an argon atmosphere. Specifically, the temperature is increased to 480℃ at a rate of 15℃ / min and kept at a constant temperature for 2 hours; then the temperature is increased to 800℃ at the same rate and kept at a constant temperature for 0.5 hours.
[0071] Step 4: Graphitization step: The composite precursor of multiple coal types obtained in step 3 is placed in a continuous graphitization furnace and heated to 2700℃ according to the preset heating curve for graphitization treatment, and held at the highest temperature for 15 hours.
[0072] Step 5: Post-processing step: The coal-based graphite obtained in step 4 is further coated using a traditional melt coating process. Then, it is screened, demagnetized, and packaged to obtain the coal-based fast-charging graphite anode material.
[0073] Step 6: Fabrication of fast-charging battery: Assemble the coal-based fast-charging graphite, conductive carbon black, and binder prepared in step 5 into a battery according to the method in GB / T44027.1-2024, and test its electrochemical performance.
[0074] Example 5:
[0075] Step 1: Select long-flame coal (vitrinite content 72%) as coal type A, reduce its ash content to 3.0 wt% through gravity separation and flotation processes, and then grind it to a D50 of 4 μm; select Guizhou anthracite (fixed carbon content 88%) as coal type B, reduce its ash content to 5.0 wt% through gravity separation and flotation processes, and then grind it to a D50 of 15 μm; select bituminous coal as coal type C, reduce its ash content to 2.0 wt% through gravity separation and flotation processes, and then grind it to a D50 of 4 μm;
[0076] Step 2: Add coal type A and coal type B to the mechanical fusion machine at a mass ratio of 1:3. Start the mechanical fusion machine and run it for 25 minutes. Under mechanical force, coal type A will be embedded into the surface of coal type B. The fused mixture will be heated to 700℃ at a rate of 2℃ / min and held at that temperature for 3 hours to obtain pre-carbonized material.
[0077] Step 3: Bonding and In-situ Hole Formation: The pre-carbonized material of the mixture of coal type A and coal type B obtained in Step 2 is mixed with coal type C at a mass ratio of 100:12. After uniform mixing, the second stage of heat treatment is carried out under a helium atmosphere. Specifically, the temperature is increased to 500℃ at a rate of 16℃ / min and kept at a constant temperature for 2 hours; then the temperature is increased to 900℃ at the same rate and kept at a constant temperature for 0.5 hours.
[0078] Step 4: Graphitization step: The composite precursor of multiple coal types obtained in step 3 is placed in an experimental induction graphitization furnace and heated to 2400℃ according to the preset heating curve for graphitization treatment. The temperature is then held at the highest temperature for 16 hours.
[0079] Step 5: Post-processing steps: The coal-based graphite obtained in Step 4 is sequentially screened, demagnetized, and packaged to obtain coal-based fast-charging graphite anode material.
[0080] Step 6: Fabrication of fast-charging battery: Assemble the coal-based fast-charging graphite, conductive carbon black, and binder prepared in Step 5 into a battery according to the method in GB / T44027.1-2024, and test its electrochemical performance.
[0081] Table 1
[0082]
[0083] Comparative Example 1:
[0084] Step 1: Select Taixi anthracite (fixed carbon content of 88%), and use gravity separation and flotation processes to reduce its ash content to 2.0wt%. Then grind it to D50 of 8μm, and (D90-D10) / D50=1.8.
[0085] Step 2: Heat the anthracite obtained in Step 1 to 900℃ at a rate of 5℃ / min and hold for 2 hours to obtain pre-carbonized material.
[0086] Step 3: Graphitization step: Place the pre-carbonized material obtained in Step 2 into the Atchison crucible graphitization furnace, heat it to 2800℃ according to the preset heating curve for graphitization treatment, and hold it at the highest temperature for 20 hours.
[0087] Step 4: Post-processing steps: The coal-based graphite obtained in Step 3 is sequentially screened, demagnetized, and packaged to obtain coal-based fast-charging graphite anode material.
[0088] Step 5: Fabrication of fast-charging battery: Assemble the coal-based graphite, conductive carbon black, and binder prepared in Step 4 into a battery according to the method in GB / T44027.1-2024, and test its electrochemical performance.
[0089] Comparative Example 2:
[0090] Step 1: Select long-flame coal (vitrinite content 70%) as coal type A, reduce its ash content to 1.5wt% through gravity separation and flotation processes, and then grind it to D50 of 12μm;
[0091] Step 2: Heat the long-flame coal obtained in Step 1 to 900℃ at a rate of 3℃ / min and hold for 4 hours to obtain pre-carbonized material.
[0092] Step 3: Place the pre-carbonized material obtained in Step 2 into an experimental induction graphitization furnace, heat it to 2800℃ according to the preset heating curve for graphitization treatment, and hold it at the highest temperature for 20 hours.
[0093] Step 4: Post-processing steps: The coal-based graphite obtained in Step 3 is sequentially screened, demagnetized, and packaged to obtain coal-based fast-charging graphite anode material.
[0094] Step 5: Fabrication of fast-charging battery: Assemble the coal-based graphite, conductive carbon black, and binder prepared in Step 4 into a battery according to the method in GB / T44027.1-2024, and test its electrochemical performance.
[0095] Comparative Example 3:
[0096] Step 1: Select low-ash lean coal (vitrinite content 70%), reduce its ash content to 3.5wt% through gravity separation and flotation processes, and then grind it to D50 of 2μm; select Taixi anthracite (fixed carbon content 88%), reduce its ash content to 4.0wt% through gravity separation and flotation processes, and then grind it to D50 of 10μm;
[0097] Step 2: Add lean coal and anthracite to a powder mixer at a mass ratio of 1:5 and mix evenly. Then, heat the mixture to 750℃ at a rate of 5℃ / min and keep it at that temperature for 2 hours to obtain pre-carbonized material.
[0098] Step 3: Place the pre-carbonized material of multiple coal types obtained in Step 2 into an experimental induction graphitization furnace, heat it to 2800℃ according to the preset heating curve for graphitization treatment, and hold it at the highest temperature for 20 hours.
[0099] Step 4: Post-processing steps: The coal-based graphite obtained in Step 3 is sequentially screened, demagnetized, and packaged to obtain coal-based fast-charging graphite anode material.
[0100] Step 5: Fabrication of fast-charging battery: Assemble the coal-based fast-charging graphite, conductive carbon black, and binder prepared in Step 4 into a battery according to the method in GB / T44027.1-2024, and test its electrochemical performance.
[0101] Comparative Example 4:
[0102] Step 1: Select low-ash long-flame coal (vitrinite content 65%) from Shaanxi region, reduce its ash content to 5.0wt% through gravity separation and flotation processes, and then grind it to D50 of 2μm; select coking coal, reduce its ash content to 5.0wt% through gravity separation and flotation processes, and then grind it to D50 of 4μm;
[0103] Step 2: Heat the long-flame coal to 900℃ at 3℃ / min and keep it at that temperature for 2 hours to obtain pre-carbonized material.
[0104] Step 3: Thoroughly mix the pre-carbonized material obtained in Step 2 with the coking coal, then heat it to 500℃ at a rate of 16℃ / min and keep it at that temperature for 2 hours; then heat it to 900℃ at the same rate and keep it at that temperature for 0.5 hours.
[0105] Step 4: Place the composite precursor obtained in Step 3 in an experimental induction graphitization furnace and heat it to 2800℃ according to the preset heating curve for graphitization treatment. Hold it at the highest temperature for 16 hours.
[0106] Step 5: The coal-based graphite obtained in Step 4 is sequentially screened, demagnetized, and packaged to obtain coal-based fast-charging graphite anode material.
[0107] Step 6: Fabrication of fast-charging battery: Assemble the coal-based graphite, conductive carbon black, and binder prepared in step 5 into a battery according to the method in GB / T44027.1-2024, and test its electrochemical performance.
[0108] Table 2
[0109]
[0110] Contents not described in detail in this specification are prior art known to those skilled in the art. Although illustrative specific embodiments of the invention have been described above to facilitate understanding by those skilled in the art, it should be understood that the invention is not limited to the scope of the specific embodiments. Various modifications are readily apparent to those skilled in the art as long as they fall within the spirit and scope of the invention as defined and determined by the appended claims, and all inventions utilizing the concept of this invention are protected.
Claims
1. A method for preparing a fast-charging graphite anode material with synergistic effects of multiple coal types, characterized in that, Includes the following steps: Step 1: Reduce the ash content of coal types A, B, and C to 0.5-5 wt% through gravity separation and flotation processes. Step 2: Coal type A is embedded into the surface of coal type B through mechanical fusion. Under an inert atmosphere, the temperature is increased to 650-900℃ at 0.5-5℃ / min for the first stage of heat treatment. The temperature is held for 2-4 hours to obtain a pre-carbonized material of the mixture of coal type A and coal type B. Step 3: Mix the pre-carbonized material of the mixture of coal type A and coal type B with coal type C; Under an inert atmosphere, the temperature is increased to 350-500℃ at a rate of 10-20℃ / min for the second stage of heat treatment, and held at the temperature for 2-3 hours. Then, the temperature is increased to 700-900℃ at the same rate and held at the temperature for 0.5-1 hours to form a composite precursor of multiple coal types. Step 4: The composite precursor of multiple coal types is heated to 2300℃~2800℃ according to the heating curve, and graphitized. The temperature is held for 10~24 hours to obtain coal-based graphite. Step 5: The coal-based graphite is sequentially screened, demagnetized, and packaged to obtain coal-based fast-charging graphite anode material; The mass ratio of coal type A to coal type B is 1:2 to 1:5; the mass ratio of pre-carbonized material of the mixture of coal type A and coal type B to coal type C is 100:(5 to 20); The A type of coal is easily graphitized coal, selected from lignite or long-flame coal with a vitrinite content ≥60%; the median particle size D50 of the A type of coal is 0.5~5μm; The B coal type is a structural skeleton coal, selected from one or more of anthracite and lean coal with an inertinite content ≥50%; the median particle size D50 of the B coal type is 8~15μm. The C type of coal is a caking and porous coal, selected from one or more of gas coal, gas-rich coal, 1 / 3 coking coal, coking coal, lean coal or fat coal; the median particle size D50 of the C type of coal is 1~5μm; In step 1, the grinding particle size of coal type A must also meet the requirement of (D90-D10) / D50≤0.8, the grinding particle size of coal type B must also meet the requirement of (D90-D10) / D50≤1.6, and the grinding particle size of coal type C must also meet the requirement of (D90-D10) / D50≤2.
0. In step 2, coal type A is embedded into the surface of coal type B through mechanical fusion, and the effect is such that the surface peeling force for separating coal type A from coal type B is 0.08~0.12 N / mm.
2. The preparation method of a fast-charging graphite anode material with synergistic effects of multiple coal types according to claim 1, characterized in that: In step 1, the volatile matter content of coal type A is ≥30%, and the fixed carbon content of coal type B is ≥75%.
3. The preparation method of a fast-charging graphite anode material with synergistic effects of multiple coal types according to claim 1, characterized in that: In step 1, coal type C contains inorganic sulfur, mainly FeS2, and its content is 1~5 wt%.
4. The preparation method of a fast-charging graphite anode material with synergistic effects of multiple coal types according to claim 1, characterized in that: In step 2, when coal type A is embedded into the surface of coal type B through mechanical fusion, 1-5 wt% of binder is added, and mechanical fusion is carried out at a high temperature of 10-50°C above the softening point of asphalt; the binder is selected from one or more of resin, asphalt, starch, and lignin.
5. The preparation method of a fast-charging graphite anode material with synergistic effects of multiple coal types according to claim 1, characterized in that: The inert atmosphere in step 2 is a mixture of hydrogen and an inert gas, with hydrogen accounting for 5-10% of the volume; the inert gas is one or more of nitrogen, argon, and helium.
6. A fast-charging graphite anode material with synergistic effects on multiple coal types, characterized in that, The fast-charging graphite anode material prepared by any one of claims 1 to 5 has a hierarchical pore structure, including micropores of <2 nm originating from coal type A, mesopores of 2-50 nm originating from sulfur etching of coal type C, and macropores of >50 nm between secondary particles.
7. An ion battery, comprising a fast-charging graphite anode material with synergistic effects of multiple coal types prepared by the method of claim 1, characterized in that: The coal-based fast-charging graphite anode material, conductive agent, and binder were assembled into a battery according to the method of GB / T44027.1-2024, and its electrochemical performance was tested; and NCA was used as the positive electrode to assemble a fast-charging battery with fast charging characteristics of 6C or higher and internal resistance ≤15mΩ.
8. An ion battery according to claim 7, characterized in that: The negative electrode employs a layered coating method to ensure that the longitudinal surface density difference of the negative electrode is ≤0.12 mg·cm³. -2 After roller pressing, its compacted density should be controlled below 1.5 g / cm³; the nitrogen specific surface area of the conductive agent used should be ≤20 m². 2 / g.
Citation Information
Patent Citations
Fast-charging graphite composite material and preparation method thereof
CN115974114A
Quick-charging graphite composite material, preparation method thereof and battery
CN117342552A
Anthracite-based graphite negative electrode material and preparation method thereof
CN118851165A
Anthracite-based fast-charging type carbon negative electrode material and preparation method thereof
CN120261569A
Multi-coal-type composite sodium battery hard carbon negative electrode material, preparation method and application
CN120553686A